The effects of medium-chain triacylglycerol and carbohydrate ingestion on ultra-endurance exercise performance - Goedecke, J. H.; Clark, V. R.; Noakes, T. D.; Lambert, E. V. (International Journal of Sport Nutrition and Exercise Metabolism, 2005)
The aims of the study were to determine if medium-chain triacylglycerol (MCT), ingested in combination with carbohydrate (CHO), would alter substrate metabolism and improve simulated competitive ultra-endurance cycling performance. Eight endurance-trained cyclists took part in this randomized, single-blind crossover study. On two separate occasions, subjects cycled for 270 min at 50% of peak power output, interspersed with four 75 kJ sprints at 60 min intervals, followed immediately by a 200 kJ time-trial. One hour prior to the exercise trials, subjects ingested either 75 g of CHO or 32 g of MCT, and then ingested 200 mL of a 10% CHO (wt/vol) solution or a 4.3% MCT + 10% CHO (wt/vol) solution every 20 min during the CHO and MCT trials, respectively. During the constant-load phases of the 270 min exercise trial, VO2, RER, and heart rate were measured at 30 min intervals and gastro-intestinal (GI) symptoms were recorded. There was no difference in VO2 or RER between the MCT and CHO trials (P = 0.40). Hourly sprint (P = 0.03 for trial x time interaction) and time-trial times (14:30 ± 0.58 vs. 12:36 ± 1:6, respectively, P < 0.001) were slower in the MCT than the CHO trial. Half the subjects experienced GI symptoms with MCT ingestion. In conclusion, MCTs ingested prior to exercise and co-ingested with CHO during exercise did not alter substrate metabolism and significantly compromised sprint performance during prolonged ultra-endurance cycling exercise.